Association Between BRCA Status and Triple-Negative Breast Cancer: A Meta-Analysis - Chen, Haixia; Wu, Jianming; Zhang, Zhihong; Tang, Yong; Li, Xiaoxuan; Liu, Shuangqing; Cao, Shousong; Li, Xianzhu (Frontiers in Pharmacology, 2018)
Triple-negative breast cancer (TNBC) is a subtype of aggressive breast cancer and characterized by a lack of the expression of estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2. BRCA genes are tumor-suppressor genes that are involved in DNA damage repair and mutations of BRCA genes may increase the risk of developing breast cancer and/or ovarian cancer due to defective DNA repair mechanisms. However, the relationship between BRCA status and TNBC needs to be further investigated and validated. The aim of this meta-analysis was to evaluate the association between BRCA status and TNBC. We systematically searched the electronic databases of MEDLINE (PubMed), Embase and Cochrane Library to identify relevant publications from April, 1959 to November, 2017. The data from the studies were examined by a meta-analysis using STATA software to calculate the odds ratio (OR) with 95% confidence interval (CI) by fixed-effect and random-effect models. We identified 16 qualified studies from 527 publications with 46,870 breast cancer patients including 868 BRCA1 mutations (BRCA1Mut) carriers, 739 BRCA2 mutations (BRCA2Mut) carriers, and 45,263 non-carriers. The results showed that breast cancer patients with BRCA1Mut carriers were more likely to have TNBC than those of BRCA2Mut carriers (OR: 3.292; 95% CI: 2.773-3.909) or non-carriers (OR: 8.889; 95% CI: 6.925-11.410). Furthermore, high expression of nuclear grade and large tumor burden (> 2 cm) were significantly more common in breast cancer patients with BRCA1Mut carriers than those of BRCA2Mut carriers (OR: 2.663; 95% CI: 1.731-4.097; P = 0.211) or non-carriers (OR: 1.577; 95% CI: 1.067-2.331; P = 0.157). The data suggest that breast cancer patients with BRCA1Mut are more likely to have TNBC, high nuclear grade and larger tumor burden.